2022
DOI: 10.1186/s12905-022-01741-x
|View full text |Cite
|
Sign up to set email alerts
|

Survey of incidence, lifetime prevalence, and treatment of self-reported vulvovaginal candidiasis, United States, 2020

Abstract: Background Vulvovaginal candidiasis (VVC) is a common gynecologic problem in the United States but estimates of its true incidence and prevalence are lacking. We estimated self-reported incidence and lifetime prevalence of healthcare provider-diagnosed VVC and recurrent VVC (RVVC), assessed treatment types, and evaluated demographic and health-related risk factors associated with VVC. Methods An online survey sent to 4548 U.S. adults; data were wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 18 publications
2
13
1
Order By: Relevance
“…Similar prevalence rate (32.7%) was observed in India 16 . On the other hand, higher rates (43%, 57.3% and 58.5%) 3,19,20 and lower rate (5%) 21 were reported in previous studies.…”
Section: Various Species Of Candida Ie C Albicans and Non-albicanscontrasting
confidence: 47%
“…Similar prevalence rate (32.7%) was observed in India 16 . On the other hand, higher rates (43%, 57.3% and 58.5%) 3,19,20 and lower rate (5%) 21 were reported in previous studies.…”
Section: Various Species Of Candida Ie C Albicans and Non-albicanscontrasting
confidence: 47%
“…In this study, we find that up to 30% of RVVC patients had one or more of the above problems. In a very recent self-reported study, Benedict et al reported that 5.2% (98/1869) of women respondents in the USA had VVC, and of those, 4.7% (5/98) were RVVC ( 14 ). This compares strikingly with 53% (43/81) of VVC patients in Iran who experienced RVVC in a study by Arastehfar et al ( 8 ), while we found 11.76% (20 cases) of RVVC in 170 patients with signs and symptoms of vaginal infection.…”
Section: Discussionmentioning
confidence: 99%
“…Vulvovaginal candidiasis (VVC) is characterized by acute inflammation leading to disease symptoms such as vaginal itching, burning, pain, redness, and vaginal discharge [ 43 ]. VVC is common and estimated to afflict 70–75% of women at least once during their lives, with over 5% experiencing several episodes within a year (recurrent vulvovaginal candidiasis, RVCC) [ 43 , 69 , 70 ]. Most cases occur in otherwise healthy, immunocompetent women [ 43 , 69 , 70 ], which differentiates VVC from oropharyngeal candidiasis.…”
Section: Special Aspects Of Vulvovaginal Candidiasismentioning
confidence: 99%